Integration of music in the english clasroom in order to teach basic vocabulary - Padilla T., Verónica; Ortiz O., Mayra
The main topic developed in this work is based on different concepts of intelligences and phrases of some writers, who think that music is the best tool to acquire knowledge according to the musical intelligence, created by Dr. Howard Gardner. The principal purpose of this theory is to recognize the existence of seven different and independent types of intelligences which are able to interact and enhance each other. Then, we will focus on one of these intelligences; in this case we chose the musical intelligence, which is the ability to perceive, transform, and express ideas or thoughts through music. Moreover, we provide some tools, activities, techniques, and strategies which can help teachers to work with any area, content, or objective they have planned during the year. In addition, we propose a reconceptualization of the teacher´s role and the work he/she plays in the classroom. Furthermore, we propose new choices in order to arrange the classroom considering that the classroom is one of the most important factors necessary to obtain significant knowledge. We chose the musical intelligence over the other intelligences because we have designed activities that we consider to be attractive, helpful and of great interest to young people of 16. Teenagers are very interested in music that is popular and they prefer to learn English through tasks that are centered on music and musical themes. In our experience as teachers, music has been a great tool to capture the students´ attention in order to get them to enjoy English.